Information-Sensitive and Customizable Service Chains - Vision and Requirements - Filipowska, Agata; Kaczmarek, Monika (Sterowane informacją łańcuchy usług - wizja i wymagania dla narzędzi, 2010)
Nowadays, service-oriented organizations while producing and delivering their products cooperate with a number of entities. Thus, service chains emerge. Although difficult to manage, as single services are under supervision of different entities, service chains, in comparison to typical business processes, are more reactive to changes and may be easily suited to specific needs of customers. Within our research, we target at the development of a next generation application supporting the lifecycle of information-sensitive and customizable service chains meeting customer expectations towards agile business processes and business services, respectively.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 147, s. 138-146
Keywords: service chains; business process managements; adaptive workflows